Penyelenggaraan Manajemen Sekolah Dan Pendidikan Perguruan Tinggi Kristen Berbasis Standar Iso 21001 - Yakub Hendrawan Perangin Angin; Tri Astuti Yeniretnowati (Discreet: Journal Didache of Christian Education, 2022)
Many Christian education school organizations and Christian religious colleges act in a less Christian way than some public education schools and public colleges, this is because most Christian education organizations lack clear benchmarks of success and Christian organizations usually emphasize on mutual allegiance to a higher purpose. Along with these problems, especially in the governance of the organization of Christian religious education schools and colleges, the ISO 21001:2018 standard has been present for the first time in the world which provides guidance to assist education service providers in providing better services. implementing ISO 21001:2018 is an educational organization that has implemented its education governance with TQM. This study uses a literature study that specifically looks at the eleven quality management principles that are the foundation of the management system of educational organizations in the world and the benefits that can be obtained by schools and colleges and how the strategies are applied, so that the governance of Christian education schools and Christian religious colleges can more quality. The eleven principles of quality management in the management system of educational organizations are: First, Focus on students and other beneficiaries. Second, visionary leadership. Third, HR Engagement. Fourth, the process approach. Fifth, continuous or continuous improvement. Sixth, evidence-based decisions. Seventh, Relationship management. Eighth, social responsibility. Ninth, Accessibility and equity. Tenth, ethical behavior. Eleventh, data protection and security.